Nusyuz and Domestic Violence: Qira’ah Mubadalah Perspective On Q.S. An-Nisa’ [4]: 34 and 128 In Jepara - Fatimah, Zulfa Wardatul; Fatah, Abdul (LP2M IAIN kUDUS, 2026)
This article examines the concept of nusyuz in Q.S. al-Nisa’ [4]:34 and 128 through the lens of Qira’ah Mubadalah and explores its relevance to cases of domestic violence in Jepara Regency, Indonesia. The study employs a qualitative approach combining library research with empirical field data obtained through in-depth interviews with five survivors of domestic violence in Jepara. The findings reveal four forms of domestic violence experienced by the participants: physical, psychological, sexual, and economic violence, including neglect of household responsibilities. The study further indicates that domestic violence is associated with misinterpretations of religious texts, gender stereotypes, the assumption that nusyuz applies exclusively to wives, and patterns of manipulation within marital relationships. To critically reassess the concept of nusyuz, this study applies the three analytical principles of Qira’ah Mubadalah to the interpretation of Q.S. al-Nisa’ [4]:34 and 128. The analysis demonstrates a significant shift from conventional interpretations that predominantly construe nusyuz as a wife’s disobedience toward her husband. Through the Mubadalah perspective, nusyuz is understood more reciprocally as any behavior by either spouse that undermines the integrity, harmony, and sustainability of the marital relationship. This reinterpretation emphasizes reciprocity, equality, and mutual responsibility between husbands and wives. The study argues that a gender-sensitive understanding of nusyuz can contribute to preventing the legitimization of domestic violence and provide a more equitable framework for interpreting Qur’anic teachings on marital relations.